Investigations of Air-Flow Configuration, Heat Transfer Behavior and Thermal Performance in Heat Exchangers with XVB-Type Turbulence Generators Under Turbulent Flow Conditions - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2025)
This study employs numerical modeling using the finite volume method to analyze airflow and thermal structures when vortex flow (VTF) generators are installed in heat exchanger square ducts (HX-SD). The VTF generator used in this study is the X-V baffle (XVB), which is designed to enhance heat transfer rates. The XVB is an evolution of the V-baffle, a type of VTF generator known for its efficiency in improving heat transfer. It features an X-shaped structure (considered in the cross-sectional (CS) plane, y-z plane) to further optimize the design. The present research investigates the effects of XVB thickness, represented by the thickness ratio (b) to the HX-SD height (H) or hydraulic diameter (Dh) (b/H), with B-R values ranging from 0.05 to 0.20. Additionally, three XVB configurations (Types A, B, and C) are examined, along with two airflow directions: AFD-VD (airflow direction – V-Downstream) and AFD-VU (airflow direction – V-Upstream). The investigation focuses on turbulent flow conditions, analyzing air velocity within a Reynolds number range of Re = 3,000 to 16,000. The results indicate that VTF is generated throughout the HX-SD due to the pressure difference caused by flow obstruction from the XVB in all cases examined. By enhancing air mixing and disrupting the thermal boundary layer (Th-BL), the induced VTF significantly increases the heat transfer rate. The maximum observed increase in heat transfer was 7.95 times higher than that of a smooth, empty duct.
Keywords: computational fluid dynamics; passive method; thermal enhancement factor; XVB